n Vergelykende vrugmorfogenetiese studie van Macadamia Integrifolia (Maidenen Betche) en Faurea Speciosa (Welw.) (Proteaceae) - Holtzhausen, Lucas Cornelius (University of Pretoria, 2022)
Thesis (DSc (Agric))--University of Pretoria, 1986.